Respuesta :

Answer:

  • Ca²⁺ (aq) + CO₃²⁻ (aq) ⟶ CaCO₃ (s)

Explanation:

1. Write the balanced molecular equation(given):

  • Ca(NO₃)₂ (aq) + Na₂CO₃ (aq) ⟶ CaCO₃ (s) + 2NaNO₃ (aq)

Notice that I replaced Fe(NO₃)₂ with Ca(NO₃)2 because Fe does not appear in the products.

2. Write the aqueous ionic compounds in form of ions:

  • Ca(NO₃)₂ (aq) ⟶ Ca²⁺ (aq) + 2NO₃⁻ (aq)

  • Na₂CO₃ (aq) ⟶ 2Na⁺ + CO₃²⁻ (aq)

  • 2NaNO₃ (aq) ⟶ 2Na⁺ (aq) + 2NO₃⁻ (aq)

3. Write the overall ionic equation

In the balanced molecular molecular equation, substitute the ionic compounds with the corresponding ions:

Ca²⁺(aq) + 2NO₃⁻(aq) + 2Na⁺ (aq) + CO₃²⁻(aq) →

                                                         CaCO₃(s) + 2NO₃⁻(aq) + 2Na⁺(aq)

4. Write the net ionic equation

Remove the spectator ions (those that appear equal on both sides):

  • Ca²⁺ (aq) + CO₃²⁻ (aq) → CaCO₃ (s) ← answer